Comparing COVID-19 vaccines for their characteristics, efficacy and effectiveness against SARS-CoV-2 and variants of concern: a narrative review. (February 2022) - Fiolet, Thibault; Kherabi, Yousra; MacDonald, Conor-James; Ghosn, Jade; Peiffer-Smadja, Nathan
Abstract: Background: Vaccines are critical cost-effective tools to control the coronavirus disease 2019 (COVID-19) pandemic. However, the emergence of variants of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may threaten the global impact of mass vaccination campaigns. Aims: The objective of this study was to provide an up-to-date comparative analysis of the characteristics, adverse events, efficacy, effectiveness and impact of the variants of concern for 19 COVID-19 vaccines. Sources: References for this review were identified through searches of PubMed, Google Scholar, BioRxiv, MedRxiv, regulatory drug agencies and pharmaceutical companies' websites up to 22nd September 2021. Content: Overall, all COVID-19 vaccines had a high efficacy against the original strain and the variants of concern, and were well tolerated. BNT162b2, mRNA-1273 and Sputnik V after two doses had the highest efficacy (>90%) in preventing symptomatic cases in phase III trials. mRNA vaccines, AZD1222, and CoronaVac were effective in preventing symptomatic COVID-19 and severe infections against Alpha, Beta, Gamma or Delta variants. Regarding observational real-life data, full immunization with mRNA vaccines and AZD1222 seems to effectively prevent SARS-CoV-2 infection against the original strain and Alpha and Beta variants but with reduced effectiveness against the Delta strain. A decline in infection protection was observed at 6 months for BNT162b2 and AZD1222. Serious adverse event rates were rare for mRNA vaccines—anaphylaxis 2.5–4.7 cases per million doses, myocarditis 3.5 cases per million doses—and were similarly rare for all other vaccines. Prices for the different vaccines varied from $2.15 to $29.75 per dose. Implications: All vaccines appear to be safe and effective tools to prevent severe COVID-19, hospitalization, and death against all variants of concern, but the quality of evidence greatly varies depending on the vaccines considered. Questions remain regarding a booster dose and waning immunity, the duration of immunity, and heterologous vaccination. The benefits of COVID-19 vaccination outweigh the risks, despite rare serious adverse effects.